Salivary C‐reactive protein, mean platelet volume and neutrophil lymphocyte ratio as diagnostic markers for neonatal sepsis - Ahmed Omran; Abdallah Maaroof; Mai H. Saleh; Amina Abdelwahab (Brazilian Society of Pediatrics, 2018)
Objective: To assess the applicability of salivary C‐reactive protein, mean platelet volume, neutrophil-lymphocyte ratio, and platelet lymphocyte ratio in the diagnosis of neonatal sepsis. Methods: Prospective case‐control study of 70 full‐term neonates, 35 with sepsis (20 with proven sepsis and 15 with clinical sepsis) and 35 healthy controls. Serum and salivary CRP concentrations were measured by ELISA while MPV, NLR, and PLR were measured by automated blood cell counter. Results: This study showed statistically significant difference of mean salivary CRP between septic neonates and controls (12.0 ± 4.6 ng/L vs. 2.8 ± 1.2 ng/L) respectively. At a cut‐off point of 3.48 ng/L, salivary CRP showed 94.3% sensitivity and 80% specificity. Salivary CRP also showed good predictive accuracy for predicting elevated serum CRP values in septic neonates. MPV and NLR showed significant difference between septic neonates and controls (10.2 ± 1.2 fL vs. 8.0 ± 0.5 fL; 2.9 ± 1.7 vs. 1.6 ± 0.4, respectively). At a cut‐off point of 10.2 fL, MPV presented 80% sensitivity and specificity. At a cut‐off point of 2.7, NLR presented 80% sensitivity and 57.1% specificity. Conclusion: This study provides support for further studies on the usefulness of salivary CPR, MPV, and NLR as diagnostic markers for neonatal sepsis.